Proposal and evaluation of a method to implement the lean construction principles - Costella, Marcelo Fabiano; Bugnotto, Gustavo; Pinzon, Analice; Lopes, Paulo Eduardo; Dalcanton, Francieli (Brazilian Journal of Operations & Production Management, 2018)
Since there is a gap between the concepts of the lean construction philosophy and an effective method of implementation in construction companies, the objective of this paper is to propose and evaluate a method to implement the lean construction principles. The method was constructed and evaluated through the application during 120 days of an action research in a pre-cast concrete company involving both researchers and the members of the company. The lean construction implementation method has three stages (preparation, application, and deployment), and it consists of three steps in each stage, totaling 9 steps. The evaluation of the method was satisfactory since the application was methodologically successful. In addition, it resulted in a cycle time reduction of 23.5% and the share of value-adding activities increased from 57.8% to 72.6%.